Dynamic magnetic resonance imaging of tumor perfusion. - Collins, D.J (IEEE Engineering in medicine and biology magazine)
This work presents approaches and biomedical challenges of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI). DCE-MRI using small molecular weight gadolinium chelates enables noninvasive imaging characterization of tissue vascularity. Depending on the technique used, data reflecting tissue perfusion (blood flow, blood volume, mean transit time), microvessel permeability surface area product, and extracellular leakage space can be obtained. Insights into these physiological processes can be obtained from inspection of kinetic enhancement curves or by the application of complex compartmental modeling techniques. Potential clinical applications include screening for malignant disease, lesion characterization, monitoring lesion response to treatment, and assessment of residual disease. Newer applications include prognostication, pharmacodynamic assessments of antivascular anticancer drugs, and predicting efficacy of treatment. For dynamic MRI to enter into widespread clinical practice, it will be necessary to develop standardized approaches to measurement and robust analysis approaches. These include the need for commercial equipment manufacturers to provide robust methods for rapidly measuring time-varying change in T1 relaxation rates, incorporation of arterial input function into kinetic modeling processes, robust analysis software that allows input from a variety of MRI devices, and validated statistical tools for the evaluation of heterogeneity.